Jenis Tumbuhan Berguna Pada Pekarangan Masyarakat Percampuran Di Kelurahan Layana Indah Kecamatan Palu Timur Sulawesi Tengah - Septi Karina (Biology Department, Mathematics and natural science, Tadulako University, 2014)
Research with title “kind of useful plants of mixture people at Layana Indah ‘s village subdistrict of Palu Timur Sulawesi Tengah which have been made since Februari till April 2013. This research has a purpose to know various useful plants which grow at Village of Layana Indah subdistict Palu Timur Sulawesi Tengah. Method that are used in this research is take random sample at location. Base on research thereare16 kinds of useful plants that used by Kaili’s Ethnic, 6 kinds of useful plants that used by Java ‘s Ethnic at Layana Indah village everday. 2 spesies used for food at Java’s Ethnic, 4 spesies used for food at Kaili’s Ethnic, 1 species plant for ritual at Java’s Ethnic, 6 species medicine plants at Kaili’s Ethnic, 1 species plant for ritualat Java’s Ethnic, 2 species plants for ritual at Kaili’s Ethnic. 3 species decorative plants at Kaili’s Ethnic, 1 species decorative plant at Java’s Ethnic. Keywords : Etnobotani, Layana Indah’s village useful plant.